SOCIO-ECONOMIC AND ENVIRONMENTAL CONSEQUENCES OF COAL MINING IN A RURAL COMMUNITY OF EAST KALIMANTAN: - - Charles Ta’bilangi; Murlianti, Sri; Martinus Nanang; Makmur Harun; Abdul Halim Ali (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The economic growth generated by natural resources in mining areas is often used by governments to mask structural tensions between development, social inequality, and environmental degradation. This study analyzes the devastating socio-economic and ecological impacts of coal mining expansion in Gunung Asri Village (pseudonym), East Kalimantan, Indonesia. The study used qualitative data obtained from in-depth interviews with 25 informants. Informants included village elites, traditional and religious leaders, farmers, traders, mine workers, and ordinary residents, reflecting variations in occupation, education level, and socio-cultural background. The study found that the industry has generated limited material benefits through infrastructure development and employment. However, the distribution of these benefits is unequal and has resulted in significant socio-ecological damage, such as land displacement, reduced agricultural productivity, water and air pollution, health risks, and increased livelihood vulnerability. CSR programs remain compensatory and technocratic, failing to address structural inequalities or foster long-term community empowerment. This situation is exacerbated by the consolidation of exclusive local power relations tightly controlled by village elites, which limit meaningful community participation and deepen social fragmentation. Coal-based development has resulted in socio-ecological transformation without empowerment in rural mining communities